Implementation of Active Learning Type Quiz Team Improving Learning Outcomes for Vocational School Chemistry Material - Sri Lestari; Hartono Hartono; Dewi Kusmawaty (Pedagogy Review, 2022)
Abstract: Application of Active Learning Model Type Quiz Team to Improve Learning Outcomes in SMK. This study aims to determine the effect of Active Learning type Quiz Team models in improving student outcomes on electrochemical materials in class X SMK. The type of research used in this study is a classroom action research conducted two cycles with each stage of the cycle of planning, action, observation and reflection. Subject of research is class X of TP1 SMK Negeri 4 Palembang, amounting to thirty six people. The research instrument used is the test of learning outcomes, questionnaires of student interest and observation sheet for both learners and teachers. the analysis used is descriptive and guidance assessment of test results, questionnaires and observation results. The result of research of learners test through outcomes states improvement of first cycle average value equal to 45,28 the completeness are 44,44% and second cycle equals to 81,39 the completeness are 86,11%. Based on research results and discussion can be concluded that there is improvement of learning outcomes of learners from learning outcomes by using Active Learning type Quiz Team models on electrochemical materials in SMK.Keywords: quiz team, classroom action research